Influence of the long-term oven aging on the performance of the reinforced asphalt mixtures - Alnadish A.M.; Ibrahim M.R.; Aman M.Y.; Katman H.Y.B. (MDPI AG, 2023)
The long-term aging of the asphalt mixtures has become a major concern because it decreases the lifespan of the asphalt layer. In this study, the asphalt mixtures incorporating steel slag aggregates were reinforced with synthetic fibers as a novel contribution in terms of decreasing the effect of aging on the performance of the asphalt mixtures. However, different mixturesnamely, Mix0, Mix1, and Mix2were subjected to long-term oven aging to study the effect of the aging on the performance of the asphalt mixes. Mix0 consisted of coarse and fine granite aggregates, while Mix1 was composed of coarse steel slag aggregate and fine granite aggregate. Mix2 represents the reinforced asphalt mixtures incorporating coarse steel slag aggregate and reinforced with the synthetic fibers of polyvinyl alcohol, acrylic, and polyester at the proportion of 0.3% by weight of the aggregates. The conducted performance tests were resilient modulus, rutting depth, and cracking resistance. The outputs of the performance tests for the unaged asphalt mixes displayed that the mixtures incorporating coarse steel slag aggregate exhibited better performance than the mixtures containing granite aggregate. Meanwhile, the reinforced asphalt mixtures have shown a lower resilient modulus and a higher permanent deformation than the unreinforced asphalt mixes due to the elastic behavior. Otherwise, the reinforced asphalt mixtures have shown superior resistance to cracking in comparison to the unreinforced mixtures. On the other hand, the performance of the aged asphalt mixtures demonstrated that the mixtures containing granite aggregates exhibited a lower susceptibility to aging than the mixtures incorporating steel slag aggregate. Meanwhile, the performance of the aged reinforced asphalt mixtures showed that introducing synthetic fibers has decreased the effect of the long-term oven aging. 2020 by the authors. Licensee MDPI, Basel, Switzerland.